Environmentally benign tribo-systems for metal forming - Bay, Niels Oluf; Azushima, A.; Groche, P.; Ishibashi, I.; Merklein, Marion; Morishita, M.; Nakamura, T.; Schmid, S.; Yoshida, M. (CIRP ANNALS - Manufacturing Technology, 2010)
The growing awareness of environmental issues and the requirements to establish solutions diminishing the impact on working environment as well as external environment has initiated ever increasing efforts to develop new, environmentally benign tribological systems for metal forming. The present paper gives an overview of these efforts substituting environmentally hazardous lubricants in cold, warm and hot forging as well as sheet forming and punching/blanking by new, less harmful lubricants and furthermore describes other measures directed towards the same goal such as development of anti-seizure tool materials and coatings and application of structured workpiece and tool surfaces. © 2010 CIRP.
LFT Import::2019-08-05 (1897)
Keywords: Environmental impact; Lubricants; Metal forming tribology; Structured tool surfaces; Structured workpiece surfaces; Tool coatings; Tool materials